Incidence of non-target pest species and validation of IPM strategies in Bt cotton hybrids deployed with different events of cry genes - KUMAR, RISHI; MONGA, D; NITHARWAL, MUKESH; SWAMI, DINESH; SINGH, SATNAM (The Indian Journal of Agricultural Sciences, 2015)
Cotton cultivars incorporated with different events of Cry proteins were evaluated for the incidence of sucking insect pests and abundance of predators under unprotected conditions during the years, 2009 and 2010. Among the sucking pests, whitefly, leafhopper and thrip were the major pests and there was no difference in the abundance of sucking pests among different hybrids. An integrated pest management (IPM) module based on use of eco-friendly strategies was developed and evaluated for transgenic cotton cultivars carrying different events including non-Bt cotton during 2010 and 2011 and was compared with the recommended regional package of practices (RPP) involving use of selective insecticides for sucking insect pests and bollworms. Results indicated low population of leafhopper, thrips and whitefly in IPM as compared to RPP. In addition, the cotton hybrids managed by IPM practices supported higher abundance of natural enemies. The incidence of cotton leaf curl disease (CLCuD) was also less in IPM as compared to RPP module. No bollworm incidence was recorded in any of transgenic cotton hybrid in either of the modules; however IPM and RPP with non-Bt hybrid showed rosette flowers and green boll damage due to pink bollworm, which was less in IPM as compared to RPP. IPM module resulted in low cost of insecticidal sprays and increase in C: B ratio compared to RPP. Furthermore, as the hybrids carrying different events did not differ significantly for the incidence of sucking pests, the IPM module developed was found effective for all hybrids including non Bt cotton hybrid with some revision in the light of bollworm incidence.